If it's not what You are looking for type in the equation solver your own equation and let us solve it.
51=-4x+11
We move all terms to the left:
51-(-4x+11)=0
We get rid of parentheses
4x-11+51=0
We add all the numbers together, and all the variables
4x+40=0
We move all terms containing x to the left, all other terms to the right
4x=-40
x=-40/4
x=-10
| 9x-61=11 | | 96=84+12r | | 8(x-3)+7=2x(4-17) | | 4p-p-9+3=-30 | | 27=2+5x-2x+10 | | -5x-24=4x | | 3h-7+6=-22 | | 8c-9c=25 | | -6/4n=8 | | 18+m=8. | | x3=87 | | 8a−6=34 | | 11-5r-2r-10=-27 | | 6-v/11=14 | | 2(x+4)−5=1/3(6x+9) | | 3(2y+3)=-6y-15 | | 4c+18=54 | | 4-6w-9/27)-2=2 | | 8p-13=51 | | 3d+d-10=4(2d-8)+6 | | 78=6s+6 | | 72/56=r/7 | | 6(k-88)=18 | | 8p÷8=12÷8 | | 3^(5-x)=15/2 | | 23=3x+5(x+3) | | 23x+2=4 | | 8(-7a+6)=-7(-6+8a)+6 | | f(-10)=-10-4 | | 7d-24=53 | | 4+2(3x-8)=12 | | 53-10x=19+7x |